COVID 19 Pandemic: Challenges in Healthcare System of India - Debasruti Naik1 , Motirmoy Giri2 , Ramesh Nagarajappa3, Ipsita Mahapatra4 , Upasana Dhar5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The new coronavirus virulent disease is stretching the health organisations worldwide and because of thisthe growing demand for health services and health care workers rapidly increasing. This emergency hasencouraged the researchers to get more serious about the deadly unknown virus. Gradually within 3 months,the virus kept spreading all over the world by direct or indirect contact with the affected people. “The bestdefence against any outbreak is a strong health system”. Focusing on COVID 19 associated actions, as wellas progressing to endow with necessary services, is significant not only to sustain people’s belief in thehealth system to distribute essential health services but also to lessen an increase in morbidity and mortalityfrom other health conditions. This review article discusses the existing healthcare resources of India and theimpact on healthcare scenario of India during this outbreak.